RUBELLA RASH (Conferencea, 2022)
Rubella is a viral infection that can cause adenopathy, rash, and sometimes systemic symptoms that are usually mild and short-lived. Exposure to rubella during early pregnancy can cause miscarriage, stillbirth, or birth defects.